2021
DOI: 10.3390/ijms22041913
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Human Antibodies against Severe Acute Respiratory Syndrome Coronavirus 2 Isolated from a Human Synthetic Fab Phage Display Library

Abstract: Since it was first reported in Wuhan, China, in 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic outbreak resulting in a tremendous global threat due to its unprecedented rapid spread and an absence of a prophylactic vaccine or therapeutic drugs treating the virus. The receptor-binding domain (RBD) of the SARS-CoV-2 spike protein is a key player in the viral entry into cells through its interaction with the angiotensin-converting enzyme 2 (ACE2) receptor protein, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Phage display has been one of the most powerful drug discovery technologies to lead to the development of FDA-approved peptide and antibody drugs for various diseases (e.g., hereditary angioedema, immune thrombocytopenic purpura, rheumatoid arthritis, and uveitis) [33,45,206] The success of phage display-derived drug molecules as well as the growing interest in peptides/antibodies in the biopharmaceutical market make phage display technology a popular approach for antiviral discovery. In fact, since the beginning of the latest coronavirus outbreak, several research groups have screened phage libraries to develop neutralizing recombinant antibodies against SARS-CoV-2 [83,191,[207][208][209][210][211][212].…”
Section: Perspectivementioning
confidence: 99%
“…Phage display has been one of the most powerful drug discovery technologies to lead to the development of FDA-approved peptide and antibody drugs for various diseases (e.g., hereditary angioedema, immune thrombocytopenic purpura, rheumatoid arthritis, and uveitis) [33,45,206] The success of phage display-derived drug molecules as well as the growing interest in peptides/antibodies in the biopharmaceutical market make phage display technology a popular approach for antiviral discovery. In fact, since the beginning of the latest coronavirus outbreak, several research groups have screened phage libraries to develop neutralizing recombinant antibodies against SARS-CoV-2 [83,191,[207][208][209][210][211][212].…”
Section: Perspectivementioning
confidence: 99%
“…A previous study has shown the ability of the related SARS-CoV-1 ORF3a N terminal targeting antibodies, derived from convalescent patients' plasma, to induce the destruction of ORF3a-expressing cells by activation of the complement pathway [60]. In addition, Akerstrom et al (2006) have demonstrated that rabbit antisera specific for the N terminus of SARS-CoV-1 ORF3a (representing amino acids [15][16][17][18][19][20][21][22][23][24][25][26][27][28] resulting in a neutralising effect 48 h post infection in virus infected Vero E6 cells [61]. There was no corresponding neutralizing effect using antisera that recognized the C terminal region of SARS-CoV-1 ORF3a in two separate studies [61,62] after 2-4 days of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Phage display technology provides a robust and well-validated antibody discovery platform and has been used successfully for the isolation of several neutralising SARS-CoV-2 anti-RBD antibodies [19][20][21][22][23][24]. Anti-viral, antibody-based therapy has well-recognized advantages including high specificity and affinity, long serum half-life and desirable effector functions [25].…”
Section: Introductionmentioning
confidence: 99%
“…These are often termed “immune libraries”; (ii) libraries constructed from B cells derived from “naïve” donors, i.e., subjects who have not been specifically vaccinated, infected, or diseased in a manner that would skew the antibody repertoire. In this case, the retrieved antibodies are usually relatively low affinity and often need to be affinity matured to improve their chances of being therapeutically relevant; and (iii) synthetic human antibody libraries [ 266 268 ], which are made to resemble natural antibodies by sequence and/or structure, usually by modelling hundreds of antibodies for which sequence and X-ray crystallographic structure information is available [ 268 ]. In this third case, synthetic libraries can also be made to mimic unusual antibodies such as the pool of anti-viral VH1-69 germline antibodies that rely on CDR-H2 contacts as part of their binding capacity [ 270 272 ], or anti-viral antibodies with long CDR-H3s [ 262 ], another “phenotype” of antibody associated with some anti-viral neutralizing antibodies [ 274 276 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%